Description of Thorax X-ray and Brixia Score in Pregnancy with COVID-19 Infection - Kusuma, A. A. N. Jaya (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Based on data until December 31, 2020, confirmed cases of coronavirus disease 2019 (COVID-19) have been reached nearly 750,000 cases, COVID-19 can infect pregnant women because a reduction in the immune receptor and increase in another pro-inflammatory factor. Complications include fetal distress, premature rupture of membranes, fetal death, chorioamnionitis, preeclampsia, sepsis, renal failure, and disseminated intravascular coagulation. A serial chest X-ray is used as a basis for assessing COVID-19 progression. An experimental study in Italy proposed a scoring system known as the Brixia score divides the chest X-ray image posteroanterior or anteroposterior into 3 zones, namely, the upper, middle, and lower zones labeled as A to F, then assess the abnormalities that exist in each area with a score of 0–3, a score of ranges from 0 to 18. This score can be used to assess the severity of symptoms suffered by confirmed patients and determine the patient’s prognosis. AIM: This study aims to determine the characteristics of the chest X-ray and Brixia score in pregnancy with COVID-19 infection. METHODS: This descriptive research aims to describe the characteristics of the chest X-ray and the Brixia score in pregnancy with COVID-19 infection in pregnancy at the Department/KSM Obstetrics and Gynecology FK Udayana/Sanglah Hospital, Denpasar. This research carried out from April 2020 to March 2021. The sample of this study was all pregnant women with confirmed COVID-19 at Sanglah Hospital Denpasar during the period April 2020–March 2021. Data collected are all pregnant women who are confirmed to have COVID-19 and met the inclusion and exclusion criteria of the study. Data recorded and data tabulation is carried out according to characteristics that have been determined, then data processing is carried out descriptive. RESULTS: In pregnant patients with confirmed COVID-19 in the period from April 2020 to March 2021, there were 95 people. The highest proportion of mothers pregnant with COVID-19 infection performs antenatal care checks at midwives and Obstetric Gynecologist (47.4%) with age 20–35 years (86.3%), primipara (41.1%), age term pregnancy (74.7%), and using the abdominal method for delivery (87.4%). X-ray results that it was found that from 95 pregnant women, there were 56 pregnant women with thorax abnormal and 39 with normal conditions. The highest proportion of the X-ray results was obtained pregnant with COVID-19 infection with abnormal thorax consolidation lesions found (94.6%) and the distribution of the lesions on the right lung side (39.3%). Based on the cross-tabulated analysis, it can be seen that the consolidation lesion is found in all Brixia scores with the highest proportion in the 0–5 category, which is 80.3%. Results chest X-ray of pregnant women with COVID-19 infection with Brixia score 0–5 had the same values including pleural effusion lesions 1.8%, pulmonary edema 1.8%, and fibrotic by 1.8%. CONCLUSION: Following conclusions can be drawn: Overview of the characteristics of pregnant women with the most COVID-19 infections is at the age of 20–35 years with a primiparous pregnancy. Gestational age term gave birth by the abdominal method; abnormal chest X-ray images are more often found in patients with COVID-19 in pregnancy with consolidated lesions as well as diffuse distribution mostly on the right side of the lung; Brixia score in pregnancy with COVID-19 infection with proportion the highest is in parameter 0–5 as much as 85.7%.